Institutional Obstacles to the Investment and Innovation Development of a Firm in the Clan-Oligarchic Economic System - Soboliev Volodymyr M.; Sobolieva Mariia V. (Bìznes Inform, 2022)
The purpose of the article, taking into account mainly the normative nature of most domestic studies of the problems of investment-innovation development of the national economy, as well as the latest foreign studies of the firm theory, and based on the institutional methodology, is to carry out a positive analysis of this problem, which, on the one hand, will bring the theoretical analysis of innovative processes in the Ukrainian economy closer to modern realities, and on the other hand, will be aimed at developing more adequate ways to solve existing problems. As result of the study, it is concluded that systemic institutional obstacles to the innovative development of the Ukrainian economy are present. During the years of independence, a powerful system of informal institutions of influence on all aspects of public life was formed in the country. In fact, the lion’s share of property and power is concentrated in the hands of a small number of the most influential families of both former and current politicians, placed in key positions of law enforcement officials and the judiciary in close contact with criminal circles. The real motivation of the activities of oligarchic circles fits into the feudal-mafia mental model of thinking, making and implementing managerial decisions. Promising directions of further research on this issue are the search for conditions and factors for dismantling the clan-oligarchic system, including the following components: demonopolization of political life and balanced political representation of the main social strata; real support on the part of the State for small and medium-sized businesses on the basis of maximum deregulation; priority development of health care, education and science on the basis of at least 10 years of allocation of 5% of GDP for these needs; proper reform of the law enforcement and judicial systems.